Polygon Shape Formation for Multi-Mobile Robots in a Global Knowledge Environment - Rashid, Abdulmuttalib T.; Ali, Abduladhem A.; DIEEI, Mattia Frasca (Iraqi Journal for Electrical and Electronic Engineering, 2019)
In coordination of a group of mobile robots in a real environment, the formation is an important task. Multi- mobile robot formations in global knowledge environments are achieved using small robots with small hardware capabilities. To perform formation, localization, orientation, path planning and obstacle and collision avoidance should be accomplished. Finally, several static and dynamic strategies for polygon shape formation are implemented. For these formations minimizing the energy spent by the robots or the time for achieving the task, have been investigated. These strategies have better efficiency in completing the formation, since they use the cluster matching algorithm instead of the triangulation algorithm.